Genetic dissimilarity between sugarcane genotypes at different harvest period for brown sugar production - Jesus de Melo, Patricia; Lúcio, Alessandro Dal'Col; Marques Jeronimo Torres, Elisangela; Inês Diel, Maria; Olivoto, Tiago; Guimarães de Andrade Landell, Marcos; Michalski Lambrecht, Darlei; Luís Tischler, André; de Lima Tartaglia, Francieli (Brazilian Journal of Biometrics, 2024)
The purpose of this study was to characterize and identify the dissimilarity between sugarcane genotypes through technological and agronomic traits, in three harvest periods for brown sugar production. A randomized complete block design with four replications, using a split-plot treatment layout was used (IACSP 93-3046, RB 96-6928, IACSP 95-5094, IACSP 97-4039, SP 81-3250, IACSP 95-5000, RB 86-7515, IACSP 96-3060, IACSP 04-704, IACSP 04-656) and three harvest periods (15, 17 and 19 months of cultivation) with four replications. Technological traits related to quality parameters and agronomic traits related to the productive aspect were evaluated. According to the results, all genotypes showed a better response in the second harvest. The qualitative variables the apparent sucrose in sugarcane, total recoverable sugars and soluble solids in sugarcane showed differences between genotypes and seasons and are the ones that most contribute to the genetic divergence of brown sugar. For the production of dark colored sugar, the RB96-6928 genotype is recommended among all those evaluated, in the three growing seasons. As for the production of light-colored brown sugar, the cultivation of the genotypes IACSP 04-656 and IACSP95-5094 in season 1, the IACSP 97-4039 in season 2 and the IACSP95-5094 in season 3 is recommended.